ANALYSIS OF FINANCIAL AND NON FINANCIAL FACTOR IN PREDICTING BANK BOND RATING LISTED INDONESIA STOCK EXCHANGE - Dendi Purnama (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2019)
This study aims to analyze the effect of solvency, liquidity, profitability, bond maturity, and auditor reputation on the predictions of bond rating in the sub-sector companies of the bank. The population in this study are all bank’s sub-sector companies listed on the Indonesia Stock Exchange from 2013 to 2017. The samples in this study are 16 companies for 5 years. The analytical method used in this study is logistic regression analysis.The results showed that solvency has negative effect on bond rating predictions. Liquidity, profitability, have significant and positive effect on bond rating predictions. While the bond maturity and auditor's reputation have no significant and possitif effect on bond rating predictions.